The Effect Of Role Play On The Students’ Public Speaking Skill - Suria Suchi Dwi Putri, Rini Fadhillah Putri (CV. PUSDIKRA MITRA JAYA, 2022)
Public speaking is became one of the goals of Indonesia’s teaching and learning. The students are expected to master verbal and non-verbal communication of public speaking skill to make them able to speak well but the students have several difficulties that are faced in learning public speaking. In this case, the teacher must have ability to solve the students’ problems. This research was aimed to find out whether role play technique has the significant effect on the students’ public speaking skill or not. This research was conducted at Cerdas Murni Islamic Senior High School. The method of this research used quantitative quasi-experimental research by using pre-test and post-test design. The researcher was divided two classes into an experimental class and a control class. The researcher was chosen XI MIPA – 1 and XI MIPA – 2 as the sample. The data were collected through analyzing the students’ pre-test and post-test scores. Based on the data, the mean score of post-test was 72.38 in experimental class and 72.4 in control class. Then, the data calculated by using t-test and it was showed that tratio was 0.13 and degree of freedom (df) was 69 whereas ttable on the significance degree of 5% was 1.66. As the result, tratio was lower than ttable. It could be concluded that role play was not effective on students’ public speaking skill.